Participation of young women in sexual and reproductive health decision-making in Malawi: Local realities versus global rhetoric - Jannah M. Wigle; Stewart Paul; Anne-Emanuelle Birn; Brenda Gladstone; Monica Kalolo; Lumbani Banda; Paula Braitstein (Public Library of Science (PLoS), 2022)
Despite the global prioritization of addressing adolescent girls' and young women's sexual and reproductive health (SRH) and participatory rights, little research has examined their lived experiences in shaping their engagement in SRH decision-making processes in the global South. Further, few studies have explored how structural and societal factors influence their agency and participation. This critical and focused ethnography, informed by postcolonial feminist and difference-centred citizenship theories, conducted in Malawi (2017-2018) elicited perspectives of youth and key informants to help address these knowledge gaps. Our findings show that the effective implementation and uptake of global discourse on participation and gender equity is hindered by inadequate consideration of girls' and young women's local political, cultural and social realities. Many girls and young women demonstrate passion to participate in SRH policymaking as agents of change. However, patriarchal and gerontocratic political and social structures/institutions, and gendered and adultist norms and practices limit their active and meaningful participation in SRH decision-making. In addition, donors' roles in SRH policymaking and their prioritization of the "girl child" highlight an enduring postcolonial power over agenda-setting processes. Understanding young people's experiences of gendered participation and scrutinizing underlying systemic forces are critical steps toward realizing young women's SRH and participatory rights.